Philosophical Texts: Character Education for Minangkabau Women - Hamdan Hasibuan; Muhammad Roihan Daulay; Mowafg Masuwd (AT-TA'LIM, 2022)
This study focuses on the concept of ideal women according to Minangkabau philosophy. The criteria of the ideal women can be found in proverbs containing implicit meaning related to ethical values, namely the view about women's ideal morality. The interpretation can be comprehended from its function and purposes as a concept of moral and character education for the Minangkabau young generation. The study toward the character education for Minangkabau women is based on the interpretation meaning from the concept of Minangkabau ideal women became the basis fine art creative idea resulting in the icon of personal expression. This artwork was materialized into the painting symbolic expression/abstraction by borrowing the traditional idiom "Tangkuluak (Tekuluk)" a kind of Bundo Kanduang's formal outfit in the form of headgear as the traditional symbol of Minangkabau custom. The creation of this symbolic expression painting aims to preserve Minangkabau aesthetics through the materialization of paintings that takes the specific theme, Bundo Kanduang as the ideal woman of Minangkabau people. This study used a qualitative method presented in the form of descriptive analysis. Data were collected through interviews and observation.Â  They had emic characteristics performed in the Centre of Minangkabau Cultural Information (in Indonesia called PDIKM) in Padangpanjang and Adityawarman Museum in Padang, West Sumatra. Meanwhile, ethic research was conducted with qualitative method, namely studying the theoretical claim and interpreting the meaning of proverbs about the nobility of Bundo Kanduang.